FRENCH MILITARY PHYSICIANS IN EXTERNAL OPERATIONS: ETHICAL CHALLENGES AND PROSPECTS - LAMBLIN, A.; DUPERRET, S.; WEY, P. F.; EINAUDI, M. A. (MEDECINE LEGALE DROIT MEDICAL, 2025)
There are numerous missions for military physicians in external operations, which could lead to ethical dilemmas when values that they consider important may have to be sacrificed in favor of operational, security or other constraints or when they conflict each other with values related to the military institution. The lack of ethical reflection or response to these dilemmas can lead to serious physical or psychological symptoms for medical staff and then seriously harm the patient. The objective of this work is to make an inventory of missions that could provide ethical dilemmas in external operations, to define the factors that lead to an ethical dilemma, to objectify the means currently available to deal with them and to consider prospects for improvement.